DETERMINING THE IMPACT OF SUPPLY CHAIN CONTRIBUTORS ON FINANCIAL PERFORMANCE: MEDIATING ROLE OF SUPPLY CHAIN PERFORMANCE - Koolrojanapat, Siravit; Kerdpitak, Chayanan (International Journal of Supply Chain Management, 2019)
Purpose: With the emerging trends in supply chain management, this research aims in providing the effect of supply chain contributors including partnership, collaboration and integration on financial performance of SMEs in Thailand. It also examine the mediation impact of supply chain performance between these strategies and overall financial performance of these firms. Design: Questionnaires were designed to obtain required information from the manager, representatives and key members of SMEs in Thailand. The sample size selected is 334. The collected information is analyzed using SPSS and AMOS. Findings: The results generated depicts that there exist a significant positive association between these three supply chain contributors adopted in this study on the financial performance of firms. It also positively signifies the impact of supply chain performance on financial performance of Thailand small and medium firms. Implications: Theoretically, this study made contributions in literature related to supply chain in the context of SMEs. Practically, it allows owners and managers of SMEs to obtain benefits by adopting supply chain contributors of partnerships and integrations in their operations in order to enhance performance by attaining competitive edge. Originality: This research is considered to be the first one in analyzing the extent to which partnership, collaboration and integration strategies in a supply chain affect the performance of firms particularly SMEs in the context of Thailand.